Gamifikasi untuk Meningkatkan Kesadaran Lingkungan pada Anak Usia Dini: Studi Kasus pada Game Simulasi Merawat Tanaman - Lailita Permata; Putra, Septafiansyah Dwi; Subyantoro, Eko (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2023)
Care inining environmental sustainability in the future, is essential to show care for the surrounding living environment. Early education on environmental protection can help cultivate a love of nature. We proposed in this research to develop a game-based technology that teaches love of the environment by helping people play with plants. The Game Development Life Cycle process (GDLC) is used, with an Alpha stage test of 83.33 and a Beta stage test from 77.93. The results of research show that these gamification techniques are accepted by the public, especially children of early age.